Investigation of Microstructural and Carbon Deposition Effects in SOFC Anodes Through Modelling and Experiments - Rathore, Shambhu Singh (Curtin University, 2017)
The investigation of the SOFC anode microstructural properties affected by microstructural parameters and degradation is the focus of this research. Imaging and image processing techniques are developed to achieve quantification of the anode microstructural information. The analytical and Computational Fluid Dynamics based modelling of the microstructure including the degradation effects developed in this work will enable the microstructure optimisation for achieving performance enhancements.